Islamic Business Ethics: Construction of Balanced and Human Values - Samsul Abidin; Hasyim Muzadi (IJED: International Journal of Economy Development Research, 2022)
Abstract :Islamic economics provides guidance to humans so that they can apply ethics in all aspects of life, including in economic or business activities. in carrying out its business activities. Business ethics in Islamic economics is contained in all aspects, both production, consumption and distribution. If business ethics is applied to all business activities, it will directly be able to create balance and mutual prosperity (maslahah) which leads to the attainment of true prosperity in both the world and the hereafter (falah).